2018
DOI: 10.1016/j.trci.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of GAPT extraction on synapse loss of APPswe/PS1dE9 transgenic mice via adjusting Bcl‐2/Bax balance

Abstract: IntroductionThe degeneration of memory-focused synapses play important roles in Alzheimer's disease (AD) pathogenesis, while it is not well known how β amyloid interferes neuron apoptosis and how a herbal combination GAPT influence synapse loss and neuronal apoptosis pathways of APP/PS1 transgenic mice.MethodsThree-month and six-month APPswe/PS1dE9 transgenic mice were used. Spatial and memory ability were measured by Morris Water Maze, Neuron and synapse number were assessed by electron microscope; Aβ, Bcl-2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…Thus, we next determined the effect of serum on the presynaptic marker synaptophysin and AMPA receptor GluA1. Consistent with previous studies [ 53 , 54 ], the 8–9-month-old APP/PS1 male mouse model showed a significant decrease in synaptophysin and GluA1 expression in the DG and CA3, but not in CA1 of the hippocampus, compared to observations in the age-matched WT controls (Fig. 7A–E ; for synaptophysin, decreases of 32.6% and 47.8% in the DG and CA3, respectively; decreases of 42.5% in CA3 for GluA1).…”
Section: Resultssupporting
confidence: 94%
“…Thus, we next determined the effect of serum on the presynaptic marker synaptophysin and AMPA receptor GluA1. Consistent with previous studies [ 53 , 54 ], the 8–9-month-old APP/PS1 male mouse model showed a significant decrease in synaptophysin and GluA1 expression in the DG and CA3, but not in CA1 of the hippocampus, compared to observations in the age-matched WT controls (Fig. 7A–E ; for synaptophysin, decreases of 32.6% and 47.8% in the DG and CA3, respectively; decreases of 42.5% in CA3 for GluA1).…”
Section: Resultssupporting
confidence: 94%
“…Thus, we determined the effect of young serum on the presynaptic marker synaptophysin and AMPA receptor GluA1. Consistent with previous studies 43,44 , the 8-to 9-month-old APP/PS1 male mouse model showed a signi cant decrease in synaptophysin and GluA1 expression in the dentate gyrus (DG) and CA3, but not in CA1 of the hippocampus, compared to observations in the age-matched WT controls (Fig. 7A-E; decreases of 32.6% and 47.8% in the DG and CA3, respectively).…”
Section: Endothelial Cdk5 Overexpression Mitigates Neutrophil In Ltra...supporting
confidence: 91%
“…GAPT can increase APP/PS1 transgenic mice's brain glucose uptake and glucose transport and improve the insulin signaling pathway (Mana et al, 2019). Moreover, synapse damage ameliorated by GAPT via regulating bcl‐2/Bax balance (Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%